Nicotiana tabacum Mediated Green Synthesis of Silver Nanoparticles and Ag-Ni Nanohybrid: Optical and Antimicrobial Efficiency - Anuoluwa Abimbola Akinsiku; Joseph Adeyemi Adekoya; Enock Olugbenga Dare (Universitas Gadjah Mada, 2021)
A sustainable method was considered for the preparation of nanosilver and its allied nanoparticles. Nicotiana tabacum, an abused plant, has found an application as a bio-chemical instead of lethal chemical in the synthesis of nanoparticles. As part of green chemistry implementation, double distilled water was the solvent used for extraction. The phytochemicals present were analyzed using standard procedures. Nanoparticle synthesis was carried out at varying precursor concentrations, and the reaction was monitored with a UV-visible spectrophotometer. Another optical characterization was also achieved with photoluminescence. Other characterization involved: X-ray diffraction (XRD), transmission electron microscopy (TEM), energy dispersive X-ray (EDS), and Fourier transform infrared spectroscopy techniques (FTIR). A matched phase identification of nanosilver resembled a face-centered cubic of Ag with a mean size of 11.68 nm, and a lattice constant of 4.0862 Å. The Ag NPs displayed activity against clinical isolates of fungi, Gram-positive, and Gram-negative bacteria as the growth inhibition was significant at P < 0.05. Ag NPs obtained from the Nicotiana tabacum proved to be an antibacterial and antifungal candidate, unlike the Ag NPs derived using chemical and physical methods, which were harmful for this purpose. Both the Ag NPs and Ag-Ni NPs displayed optical activity, which qualifies them for application in visual materials.